Relation of pyloric motility to pyloric opening and closure in healthy subjects. Issue 4 (April 1992) - Tougas, G; Anvari, M; Dent, J; Somers, S; Richards, D; Stevenson, G W
Abstract : The relation between pyloric motor activity, opening, and closure was examined in eight healthy men. Manometry was performed with an assembly combining 13 side holes and a sleeve sensor positioned astride the pylorus. Simultaneous with manometry, pyloric opening and closure and antroduodenal contractions were observed fluoroscopically with the antrum filled with barium. During intraduodenal normal saline infusion, coordinated antral pressure waves swept over the pylorus and ejected barium into the duodenum. No localised pyloric motor pattern was observed under these conditions. In contrast, the intraduodenal triglyceride infusion was associated with the absence of antral pressure waves and virtual absence of antral wall movement. At the pylorus, there was a zone of luminal occlusion less than 1 cm long that persisted for the period of observation. This zone of luminal occlusion corresponded precisely with manometric recordings of a narrow zone of pyloric phasic and tonic activity. During the duodenal triglyceride infusion, the pylorus was closed for 98.5% of the measurement period when basal pyloric pressure was 4 mm Hg or more, and during this motor pattern, barium did not traverse the pylorus. Localised pyloric contractions cause sustained pyloric closure, whether these contractions are phasic or tonic. These contractions occur independently of antral or duodenal contractions and may interrupt gastric emptying.